2018
DOI: 10.5271/sjweh.3781
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to loud noise and risk of vestibular schwannoma: results from the INTERPHONE international case‒control study

Abstract: Conflicting results have been obtained about the association between exposure to occupational loud noise and risk of vestibular schwannomas (acoustic neuromas). In the largest case-control study conducted to date on this tumor, consistent associations have been observed with self-reported loud noise exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…To this end, a substantiated biological explanation behind the rising incidence rates remains absent. Although several survey-based studies have reported an association between noise exposure and the development of sporadic VS 19,20 or between cell phone use and sporadic VS, 21 several robust population-based case-control studies have refuted these claims. [22][23][24] The apparent discrepancy is most likely accounted for by the susceptibility of the aforementioned survey-based studies to recall bias, where patients who have been diagnosed with a tumor on their hearing nerve are Several incidence rates were reported in this study; however, for reasons exhaustively described in the original study, the rate of 3.3 per 100,000 personyears likely represents the most accurate estimate reported based on completeness of data.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a substantiated biological explanation behind the rising incidence rates remains absent. Although several survey-based studies have reported an association between noise exposure and the development of sporadic VS 19,20 or between cell phone use and sporadic VS, 21 several robust population-based case-control studies have refuted these claims. [22][23][24] The apparent discrepancy is most likely accounted for by the susceptibility of the aforementioned survey-based studies to recall bias, where patients who have been diagnosed with a tumor on their hearing nerve are Several incidence rates were reported in this study; however, for reasons exhaustively described in the original study, the rate of 3.3 per 100,000 personyears likely represents the most accurate estimate reported based on completeness of data.…”
Section: Discussionmentioning
confidence: 99%